Respuesta :
To solve this problem you must apply the proccedure shown below.
1. By definition, a perfect square trinomial has the following form:
[tex] a^{2}+ 2ab+b^{2} [/tex]
2. Therefore, you must divide the middle term by 2 and square the result, as following:
[tex](1/2)/2=(1/4)^{2}=1/16 [/tex]
3. As you can see, [tex] b^{2}=1/16[/tex], so, you can rewrite it as below:
[tex](x+1/16)^{2} [/tex]
The answer is: [tex]1/16[/tex]
1. By definition, a perfect square trinomial has the following form:
[tex] a^{2}+ 2ab+b^{2} [/tex]
2. Therefore, you must divide the middle term by 2 and square the result, as following:
[tex](1/2)/2=(1/4)^{2}=1/16 [/tex]
3. As you can see, [tex] b^{2}=1/16[/tex], so, you can rewrite it as below:
[tex](x+1/16)^{2} [/tex]
The answer is: [tex]1/16[/tex]
Answer: The required correct value is [tex]\dfrac{1}{16}.[/tex]
Step-by-step explanation: We are given to find the correct value so that the following expression is a perfect square trinomial :
[tex]E:x^2+\dfrac{1}{2}x+?[/tex]
Let the required number be represented by p.
Then, we have
[tex]x^2+\dfrac{1}{2}x+p\\\\\\=x^2+2\times x\times \dfrac{1}{4}+\left(\dfrac{1}{4}\right)^2+p-\left(\dfrac{1}{4}\right)^2\\\\\\=\left(x+\dfrac{1}{4}\right)^2+p-\dfrac{1}{16}.[/tex]
So, to make the given expression a perfect square trinomial, we must have
[tex]p-\dfrac{1}{16}=0\\\\\\\Rightarrow p=\dfrac{1}{16}.[/tex]
Thus, the required correct value is [tex]\dfrac{1}{16}.[/tex]